2008
DOI: 10.1585/pfr.3.s1055
|View full text |Cite
|
Sign up to set email alerts
|

Density Collapse and Fluctuation Observed in Poloidally Rotating Plasma on TU-Heliac

Abstract: The ohmic heated plasma in TU-Heliac was biased by a hot-cathode to drive E × B poloidal rotation. Coincident measurements of the line density and ion saturation currents revealed the existence of density collapse accompanied by fluctuation in the poloidally rotating plasma. The radial density profiles just before and after the collapse were estimated. The steep density gradient vanished with the density collapse. The power spectra of the fluctuation were calculated from the ion saturation current obtained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In the biased plasma, the steep density profile around the core plasma region suddenly collapsed, accompanied with high-frequency bursting turbulent fluctuation (100 kHz < f < 500 kHz). The frequency was 2-3 times the E × B plasma rotation frequency and agreed well with the frequency obtained from the dispersion relation of flute instability [13,16], in which however the time and space structure of fluctuation level were not precisely analysed. In this paper, we report the dynamic behaviour of micro-turbulence induced by electrode biasing in TU-Heliac.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the biased plasma, the steep density profile around the core plasma region suddenly collapsed, accompanied with high-frequency bursting turbulent fluctuation (100 kHz < f < 500 kHz). The frequency was 2-3 times the E × B plasma rotation frequency and agreed well with the frequency obtained from the dispersion relation of flute instability [13,16], in which however the time and space structure of fluctuation level were not precisely analysed. In this paper, we report the dynamic behaviour of micro-turbulence induced by electrode biasing in TU-Heliac.…”
Section: Introductionsupporting
confidence: 82%
“…In the biased plasma, we have observed the bursting turbulent fluctuation and density collapse in the ion saturation current with Langmuir probes [13][14][15][16][17]. Figure 3 shows typical time evolutions of electrode current I E , electron density n e , electron temperature T e and ion saturation current I s at ρ = 0.2, measured with the Langmuir probe at φ = 0 • .…”
Section: Density Collapse and Bursting Fluctuation In Tu-heliacmentioning
confidence: 99%
See 1 more Smart Citation
“…In TU-Heliac, we observed that density collapse accompanied high-frequency bursting fluctuations [3]. To survey the characteristics of the MHD fluctuations, we developed a magnetic probe sensitive to magnetic fluctuations and insensitive to capacitive pickup noises.…”
mentioning
confidence: 99%